Non-HIV AIDS presenting with adrenal histoplasmosis and pulmonary tuberculosis: a mesmerising case report and discussion - Banerjee, Arnab; Biswas, Mithun; Sarkar, Niladri (International Journal of Research in Medical Sciences, 2017)
Non-HIV AIDS or idiopathic CD4 lymphocytopenia (ICL) is an acquired immunodeficiency syndrome resulting in CD4 lymphopenia without any evidence of HIV infection or any other apparent cause of immunosuppression. A non-diabetic patient presented with adrenal histoplasmosis and UTI leading to adrenal failure. No immediate cause of immunosuppression was found, HIV, HTLV screening were negative. A CD4 count was done and the patient was found to be having non-HIV AIDS (idiopathic CD4 lymphocytopenia). He was treated and discharged. Few months later the patient presented again with adrenal failure & pulmonary tuberculosis. Adrenal FNAC showed persisting adrenal histoplasmosis. CD4 count found to be low again, but this time it was worse than the previous scenario.